2022
DOI: 10.1001/jamanetworkopen.2022.18362
|View full text |Cite|
|
Sign up to set email alerts
|

Perspectives of Latinx Individuals Who Were Unvaccinated and Hospitalized for COVID-19

Abstract: This qualitative study investigates the perspectives on vaccination of Latinx individuals who had not received a COVID-19 vaccine and were hospitalized with the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…42 Cervantes et al, found that, for unvaccinated Latinx patients in Colorado who were hospitalized with COVID-19, opportunities to have “conversations with trusted sources, such as faith-based leaders, or access websites that provided accurate and consistent information” could improve uptake of COVID-19 prevention strategies like vaccines. 43 (p. 9) The P&P text message component was well situated to serve as a trusted source of information and to offer links to accurate information.…”
Section: Discussionmentioning
confidence: 99%
“…42 Cervantes et al, found that, for unvaccinated Latinx patients in Colorado who were hospitalized with COVID-19, opportunities to have “conversations with trusted sources, such as faith-based leaders, or access websites that provided accurate and consistent information” could improve uptake of COVID-19 prevention strategies like vaccines. 43 (p. 9) The P&P text message component was well situated to serve as a trusted source of information and to offer links to accurate information.…”
Section: Discussionmentioning
confidence: 99%
“…Societal freedoms capture concerns related to what will and will not be allowed based on vaccination status including freedom of movement, freedom of vaccine choice, and freedom of speech related to the vaccine itself. Though some of these specific survey items have been identified in the literature from a single country [ 13 , 14 , 15 , 31 , 32 , 33 , 34 ] this is the first analysis to identify that these concerns were common in multiple countries at the same time. This demonstrates that concerns are not limited to one country, but rather spread across borders.…”
Section: Discussionmentioning
confidence: 99%
“…In the Original Investigation titled “Perspectives of Latinx Individuals Who Were Unvaccinated and Hospitalized for COVID-19: A Qualitative Study,” 1 published June 17, 2022, there was an error in the Results. The number of individuals who remained undecided after hospitalization should have read 5.…”
mentioning
confidence: 99%
“…The number of individuals who remained undecided after hospitalization should have read 5. This article has been corrected …”
mentioning
confidence: 99%